Design optimization of a fully integrated charge-pump with LC tank oscillator for ultra-low voltage energy harvesting. (January 2017) - Jayaweera, H.M.P.C.; Muhtaroğlu, Ali
Abstract: Model based optimization of a novel integrated interface circuit topology is presented for low voltage DC-DC step-up conversion. A cross-coupled charge pump is implemented in standard 0.18 µm CMOS technology using an integrated LC tank oscillator to enable a compact, low cost, self-starting solution with maximum efficiency at ultra-low input voltage levels available from embedded micro-power generators. The voltage doubling oscillator can start up with input as low as 0.10 V. Full system can step 0.2 V up to 1.7 V to supply >400 μW to 6 kΩ load with 46.5% efficiency based on post-layout simulations. The minimum simulated input voltage is 0.11 V, which is boosted up to 1.0 V under open circuit conditions. The optimized system thorough the established model improves output power and efficiency more than 30% compared to the alternatives. The compact LC tank leads to 17% area reduction compared to the conventional VCO with four planar inductors.